(untitled) (Ghana Journal of Science, Technology and Development, 2024)
Tracing contamination to its ultimate source is considered difficult as multiple factors affect stable microbial community in culture water. Feed, covering over 60 percent of production cost although less considered, could represent a significant source of fish diseases, the major constraint in aquaculture production. The present study based on the sensitivity of quantitative Polymerase Chain Reaction, indicated low to high concentrations of bacteria and fungi in fish-feed from various aquaculture farms in Ghana. Prevalence rate of bacteria isolated from the gut of fish (26.09%) were similar to that from diseased portions (26.89%). Although mode of transmission of most infections are largely through the water in which the fish are submerged, Staphylococcus aureus was not isolated from the culture water samples but occurred with the highest prevalence (60%) in fish-feed, thus confirming contamination of fish-feed as a significant pathway for entry of pathogens. Advancements towards the safety of fish should include the surveillance of fish-feed for microbial quality, and incorporation into human foodborne disease surveillance systems to ensure holistic effectiveness.